Selective measurement of anti-tTG antibodies in coeliac disease and IgA deficiency: an alternative pathway. Issue 1047 (7th August 2012) - Harrison, Elizabeth; Li, Ka-Kit; Petchey, Michael; Nwokolo, Chuka; Loft, Duncan; Arasaradnam, Ramesh P
Abstract : Objective: To determine the ability of selective antibody testing to screen for coeliac disease in the presence of IgA deficiency and to define the sensitivity of a pathway using this method. Method: All IgA and IgG anti-tTG tests performed at our centre between January 2008 and December 2009, using the Immunocap 250 analyser, were retrospectively reviewed. Positive results were correlated with histology. Results were used to validate our diagnostic pathway. Results: 12 289 consecutive serological tests were reviewed. IgA deficient patients gave either an 'error' reading or very low response on the Immunocap 250 analyser. Subsequent testing of this sub-group demonstrated raised IgG anti-tTG antibodies in those with histologically proven coeliac disease. Conclusions: Using our antibody screening pathway, which involves the selective use of IgG anti-tTG, sensitivity increased from 87% to 92% in those with IgA deficiency. Adoption of this pathway for coeliac screening would negate the routine screening of immunoglobulin levels, with resultant cost saving.